Analisis Pengaruh Penataan Produk, Desain, Harga, Promosi Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Toko Pusaka Batik Banyuwangi - Rani Nofi Susanti; Haifah Haifah; Hayatul Maspufah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is entitled “ Analysis of the influence of the Produk Arrangement, Design, Price, Promotion,and Service Quality, on Purchasing Decisions of the Banyuwangi Batik Heritage Store”. This research aims to determine the partial and simultaneous influence of the variables of the product arrangement, design, price, promotion, and service quality on purchasing decisions. The population and sample in the research were customers of the Banyuwangi Batik Heritage Store. The sampling tchnique used was accidental sampling. The data analysis method used multiple linear regression with the help of SPSS 20. The results showed that partially there was no influence of the variables of product arrangement, design, promotion, while the variables of price and service quality had a partial influence on purchasing decisions. For the variables of product arrangement, design, promotion, price, and service quality,there was a simultaneous influence on purchasing decisions with a calculated F values of 36.067.